Theodora : actress, empress, saint - Potter, D. S. (David Stone), 1957- (Women in antiquity., 2015)
Two of the most famous mosaics from the ancient world, in the church of San Vitale in Ravenna, depict the sixth-century emperor Justinian and, on the wall facing him, his wife, Theodora (497-548). This majestic portrait gives no inkling of Theodora's very humble beginnings or her improbable rise to fame and power. Raised in a family of circus performers near Constantinople's Hippodrome, she abandoned a successful acting career in her late teens to follow a lover whom she was legally forbidden to marry. When he left her, she was a single mother who built a new life for herself as a secret agent.